Evaluation of the effectiveness of crediting management system of agrarian enterprises - Mashchenko, Maryna; Sergienko, Olena; Dykan, V.; Dykan, O. (Global Scientific Trend, 2021)
The state of governmental support for crediting of agricultural enterprises is analyzed. A comprehensive analysis of the state of agricultural enterprises crediting is carried out in all possible areas that allows to solve the main problems of agricultural enterprises crediting in Ukraine and shortcomings in the management of financial and credit relations at different levels and to identify the main factors of influencing the development and priority directions of crediting development. The complex of tasks for assessing the effectiveness of crediting management system of agrarian enterprises is determined. The three-level management system for the agroindustrial complex is proposed: agrarian enterprises - the object of management, regional bodies - the subject of the first level management, the state - a higher level management subject.
Keywords: economics; innovation and investment activity; economic security; subjects of agribusiness